Studying the Effect of Tumor Necrosis Factor-Alpha and Tumor Necrosis Factor Gene Polymorphisms on the Incidence of Tuberculosis - Jalaledin Ghanavi; Poopak Farnia (International Journal of Mycobacteriology)
Tuberculosis and its pathogen, Mycobacterium tuberculosis complex, are a major health challenge. The causative agent of tuberculosis is M. tuberculosis complex and is transmitted through airborne droplets. Tumor necrosis factor-alpha (TNF-α) is one of the cytokines that mediate a major role in the cellular immune response to tuberculosis and is essential for pathogen clearance, control of mycobacterial growth, and facilitation of apoptosis of infected cells. Susceptibility to tuberculosis and disease progression are influenced by environmental factors and the host’s genetic predisposition. TNF polymorphisms affect disease susceptibility and patient response to drugs and treatment. Various studies have been conducted to associate TNF polymorphisms with susceptibility to tuberculosis. This activity aims to review the role of TNF-α cytokine and the impact of its polymorphisms on the occurrence of tuberculosis and compiles recent mechanistic and epidemiological findings.